1
$\begingroup$

$T$ is a tempered distribution on $\mathbb R$, $f$ is a Schwartz functions on $\mathbb R$. We define $T\ast f$ as $(T\ast f) (l)$=$T(f(-x)\ast l)$ for all $l$ Schwartz function, where the last $\ast$ is convolution. Asume $f(-x)\ast l$ is a Schwartz function and $T\ast f$ is a tempered distribution. Show that $F(T\ast f)$=$(1/(2\pi)) F(T)F(f)$ where $F$ is Fourier transform.

My idea: $F(T\ast f) (l) = T\ast f (F(l))$ Fourier transform of a tempered distribution, then $T\ast f (F(l))=T(f(-x)\ast F(l))$ definition of $T\ast f$ Now How to proceed?

$\endgroup$
  • $\begingroup$ I think it is ok now $\endgroup$ – rrrto2005 Oct 14 '14 at 2:49
  • 2
    $\begingroup$ Does your comment indicate that you completed the proof? So why not answer your own question and let us see if it is correct. $\endgroup$ – Vobo Oct 16 '14 at 16:16
1
$\begingroup$

The formula is not quite correct viz:

Let $(T|f)$ be the pairing between tempered distributions and Schwartz functions. If $f$ is Schwartz function then set $\check f(x) = f(-x)$. Also let $F$ denote the Fourier transform. We normalize so that $F^4 = I$ on the Schwartz space. If $T$ is a tempered distribution then $F(T)$ is defined by $(T|F^{-1}(f))=(F(T)|f)$. We note that if $f$ is a Schwartz function and $T$ is a tempered distribution then $T*f$ is defined by $(T|\check f *g)=(T*f | g)$. Finally here is the calculation: $$ (F(T * f)|g)= (T * f | F^{-1}(g)) = (T|\check f * F^{-1}(g)) =(T|F^{-1}(F(\check f) g)) =(F(T)|F(\check f)g)$$ So the formula is $F(T*f)=F(\check f) F(T)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.